Synthesis of N-substituted-4-methylene-oxazolidinones via base-catalyzed cyclization of propargylic alcohols with p-toluenesulfonyl isocyanate. Issue 9 (September 2020) - Pi, Shao-Feng; Guo, Yue-Meng; Zhou, Zheng-Rui; Sun, Han-zhou; Yi, Bing
A practical method is developed for the synthesis of oxazolidinone derivatives, an important class of heterocyclic compounds. The effect of bases and solvents on this cyclization reaction is discussed and a simple new base–solvent system (triethylamine in toluene) is found to be the most effective. The reaction conditions developed here are mild and no by-products are observed. Moreover, using optimized conditions, a number of differently substituted propargylic alcohols are cyclized to the corresponding N -substituted-4-methylene-oxazolidinones in yields of up to 99%.